Statin use and risk of contralateral breast cancer: a nationwide cohort study. Issue 10 (13th November 2018) - Langballe, Rikke; Cronin-Fenton, Deirdre; Dehlendorff, Christian; Jensen, Maj-Britt; Ejlertsen, Bent; Andersson, Michael; Friis, Søren; Mellemkjær, Lene
Abstract Background Statins have demonstrated antineoplastic effects in breast cancer cell lines, particularly in oestrogen receptor (ER)-negative cell lines. However, epidemiological studies have not supported a preventive effect of statin use against breast cancer. Therefore, we examined the association between statin use and contralateral breast cancer (CBC) risk among women with breast cancer. Methods We identified 52, 723 women with non-metastatic breast cancer during 1996–2012 from the Danish Breast Cancer Group database. We defined time-varying post-diagnosis statin use as minimum two prescriptions lagged by 1 year. Cox regression analyses were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for CBC associated with statin use. Results Statin use was associated with a lower CBC risk (HR = 0.88; 95% CI = 0.73–1.05). The inverse association was strongest for long-term use overall (HR = 0.64; 95% CI = 0.43–0.96), although the HR specifically for long-term consistent use and high-intensity use approached unity. Among ER-negative breast cancer patients, statin use was associated with a CBC risk reduction (HR = 0.67; 95% CI = 0.45–1.00). Conclusions We found some indication that statins reduce the risk of CBC. Further evaluations are needed to disentangle the equivocal results for long-term use and to establish if ER-negative breast cancer patients may benefit most from statin use.